AMPHETAMINE AUGMENTS VESICULAR DOPAMINE RELEASE IN THE DORSAL AND VENTRAL STRIATUM THROUGH DIFFERENT MECHANISMS - Avelar, Alicia J. (2013)
Amphetamine has well-established actions on presynaptic dopamine signaling, such as inhibiting uptake and degradation, activating synthesis, depleting vesicular stores, and promoting dopamine-transporter reversal and non-exocytotic release. Recent in vivo studies have identified an additional mechanism: augmenting vesicular release. Here we investigated how amphetamine elicits this effect. Our hypothesis was that amphetamine enhances vesicular dopamine release in dorsal and ventral striata by differentially targeting dopamine synthesis and degradation. In urethane-anesthetized rats, we employed voltammetry to monitor dopamine, electrical stimulation to deplete stores or assess vesicular release and uptake, and pharmacology to isolate degradation and synthesis. While amphetamine increased electrically evoked dopamine levels, inhibited uptake, and up-regulated vesicular release in both striatal sub-regions in controls, this psychostimulant elicited region-specific effects on evoked levels and vesicular release but not uptake in drug treatments. Evoked levels better correlated with vesicular release compared to uptake, supporting enhanced vesicular release as an important amphetamine mechanism. Taken together, these results suggested that amphetamine enhances vesicular release in the dorsal striatum by activating dopamine synthesis and inhibiting dopamine degradation, but targeting an alternative mechanism in the ventral striatum. Region-distinct activation of vesicular dopamine release highlights complex cellular actions of amphetamine and may have implications for its behavioral effects.